Correlation between experimental and theoretical study of scheelite and wolframite-type tungstates. (December 2020) - Yadav, P.; Dev Bhuyan, Prabal; Rout, S.K.; Sonvane, Yogesh; Gupta, Sanjeev K.; Sinha, E.
Abstract: Structural and optical properties of A W O 4 ( A = B a, S r, C a, M g, and Z n ) ceramics were investigated. The structural analysis confirmed the scheelite-type tetragonal structure for ( A = B a, S r and C a ) W O 4 and wolframite-type monoclinic structure for ( A = Z n and M g ) W O 4 compounds. The experimentally observed optical band gap (Eg ) found to be in the range of 4.17–5.92 eV agree with those calculated with the help of density functional theory. A decrease in band gap value with the decrease in ionic radii of A 2+ in the A W O 4 compound was observed. An intense blue-green photoluminescence emission was observed for these materials and correlated with Eg . The environmental factor h e calculated by complex chemical bond theory has been correlated with the broadening of PL excitation bands. The excitation spectra revealed that there subsists a negative relation between h e and position of energy levels.